Industry 4.0 technology implementation in the New Zealand manufacturing sector : an empirical study of influencing factors and sustainability perspectives : a thesis presented in partial fulfilment of the requirements for the degree of Master of Business Studies in Management at Massey University, Auckland, New Zealand - Wood, Vanessa M. (Massey University, 2025)
Industrialisation not only enables firms to develop and prosper but also causes social and environmental harms. Integrating Industry 4.0 technologies (I4Ts) into manufacturing processes is promoted as a way to increase the sector’s sustainability. The prevailing narrative of extant literature is that I4T implementation results in positive sustainability outcomes, with little mention of negative outcomes. I4T implementation is considered essential to increase the global competitiveness and sustainability of New Zealand’s manufacturing sector. However, little is known about the factors influencing I4T implementation in NZ manufacturing, or the contribution I4Ts make to sustainability. Consequently, this study has two objectives. One is to explore the factors influencing I4T implementation by examining its drivers, enablers, and inhibitors. The other is to explore managerial perspectives of the positive and negative contributions I4Ts make to sustainability. A qualitative research methodology was adopted, and template thematic analysis was used to analyse data gathered from fifteen semi-structured interviews with senior executives employed within and connected to the NZ manufacturing sector. Institutional theory (INT) and dynamic capabilities theory (DCT) were used to interpret the findings. The study found that NZ manufacturers employ dynamic capabilities to implement I4Ts as a strategic response to coercive and mimetic institutional forces. Key identified drivers were competitive and stakeholder pressures, data capture and analysis, I4T awareness, and labour shortages. Financial resources, skilled personnel, ERP systems, and change management were key enablers of I4T implementation. Conversely, high financial cost, lack of skilled personnel, resistance to change, and low production volumes were key inhibiting factors. This study makes several contributions. The study contributes to theory by applying INT and DCT in an integrative framework that conceptualises I4T implementation from a fresh perspective. A number of novel findings were identified that could serve as a foundation for future research. Manufacturers can use the insights gained from this study to make informed decisions about I4T implementation, including how to maximise positive and minimise negative sustainability outcomes. For policymakers, the study identified various bases for developing policies and initiatives supporting I4T implementation and sustainable manufacturing.
Figure 3.1 is adapted from the original (King & Brooks, 2017 Fig 3.1) and reproduced in accordance with the fair dealing principle.
Keywords: 401408 Manufacturing processes and technologies (excl. textiles)